Implementing the mathematical model of the throughput of compressor station aggregates - Vaszi, Zsolt; Szabó, Csaba; Varga, Augustín (Nonlinear Analysis: Modelling and Control, 2015)
The main aim of the European union energy policy is to ensure a continuous supply of natural gas for the member states. The Russian gas is transported through the Belarus, Ukraine, Slovakia (SR) and Czech Republic to Germany. This article shortly describes the transit system of Slovakia and compressor station KS1 – Vel’ké Kapušany. The throughput of this compressor station plays an important role in gas transport, because this station is the entry to the transit system of SR. To find the best combination of the aggregates used in gas transport a simulation algorithm was devised. We present the architecture of this simulation software together with the description of its development phases. The software was evaluated against data gained from the KS1 compressor station operation. The combinations of aggregates were found as dependent on inlet pressure, ambient temperature and compression ratio.